2019
DOI: 10.3390/ma12203387
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Monitoring and Material Flow Characteristics of Friction Stir Welded 2A14-t6 Aerospace Aluminum Alloy

Abstract: Aiming at the problems that the temperature in the welding area of friction stir welding (FSW) is difficult to measure and the joints are prone to defects. Hence, it is particularly important to study the material flow in the welding area and improve the welding quality. The temperature of the tool shoulder and the tool pin was monitored by the wireless temperature measuring system. The finite element model of friction stir welding was established and the welding conditions were numerically simulated. The flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…They further reported that induction of ultrasonic vibrations during welding improved material flow in the pin affected zone and aided in the elimination of tunnel defect. The occurrence of these zones was reaffirmed by Wu et al 45 in their recent study. The downward movement of shoulder driven flow and its convergence with the pin driven flow is observed in weld macrographs of Figure 5.…”
Section: Resultssupporting
confidence: 55%
“…They further reported that induction of ultrasonic vibrations during welding improved material flow in the pin affected zone and aided in the elimination of tunnel defect. The occurrence of these zones was reaffirmed by Wu et al 45 in their recent study. The downward movement of shoulder driven flow and its convergence with the pin driven flow is observed in weld macrographs of Figure 5.…”
Section: Resultssupporting
confidence: 55%
“…al. [25,26]. Furthermore, both curves are located in the diffusion-controlled transformation zone for Ti6Al4V extending from 800° C-995° C (striped area), what leads to the assumption that lamellar α-and β-titan will be present in the resulting microstructure for both joints with varying volume content.…”
Section: Process Behaviormentioning
confidence: 99%
“…The , , and represent the mean velocity in x , y , and z directions. On the other hand, the , , and are the turbulent fluctuation that are calculated by [ 34 , 35 ]: …”
Section: Process Modellingmentioning
confidence: 99%